(untitled) (Tempo e Argumento, 2012)
The text discusses some aspects of the curricular speech for the teaching of History at school, produced from the 1970`s of the twentieth century, in which contributions of knowledge coming from different fields were crossed and the way such speech is made proper by the teachers an transformed into teachable knowledge by means of the suitable distribution of the curriculum in contents for teaching. To do so, we try to articulate the school historic knowledge to different instances of production: as regards to educational policy, from what we point out the curriculum as elaborated production in different aspects by reinterpretation process of the curricular text, of the subject History as a school curricular component and as a kind of knowledge simultaneously constructed for the school and by the school, here analyzed under the school culture perspective. In another interface, we discuss some aspects of teacher ́s practices seen in this study as a result of a complex process, in which the academic knowledge as well as other kinds of knowledge resulting from teaching experience are present. Under such perspective, we consider the action of the State as formulator of public policies as determinant for the concretization of its curricular proposal(s) in the school scenario through different mechanisms: selection and organization of teaching programs contends, teaching procedures prescriptions, external evaluation promotion and didactic book(s) selection processes, among others. However, we agree with Marin & Sampaio (2004) on that the inclusion of teachers in the process of curricular reforms proposed by the State is fundamental for their success.